Measuring the Prevalence of Interpersonal Violence Victimization Experience- and Self-Labels: An Exploratory Study in an Alaskan Community-Based Sample - Johnson, Ingrid Diane (Journal of family violence, 2024)
Purpose: How victims of violence against women (VAW) label their experiences and selves can be important for help-seeking, but descriptive research on the prevalence of experience- and self-labels among VAW victims is limited. This study sought to fill some of the gaps in this quantitative literature using new measurement tools. Method: The current study used quantitative survey data from a weighted sample of 1694 community-based women in Alaska who had experienced VAW (determined using behaviorally specific items) to measure the prevalence of a variety of labels these victims could apply to their experiences and selves. Results: Generally, victims of specific forms of violence had minimal agreement on the terms they used to label their experiences. The most commonly endorsed label was 28.5% of those who had experienced alcohol or drug involved sexual assault applying the label rape to their experiences. Across all victims, the most commonly endorsed self-label was survivor, with one-quarter to one-third endorsing this label, depending on the subsample. Roughly one-tenth used the self-label victim across all subsamples. Conclusion: VAW service providers should consider labels used to promote services and how to increase awareness about which behaviors constitute VAW; policymakers should improve the accessibility of healthcare so that labeling oneself or one’s experiences in a certain way is not a prerequisite of help-seeking; and researchers should continue exploring how to measure experience- and self-labels with minimal priming of participants and greater specificity to the actual experiences with violence.